2009
DOI: 10.1161/atvbaha.108.172676
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 Exocytosis Is Stimulated by Sphingosine-1-Phosphate in Human Blood and Lymphatic Endothelial Cells

Abstract: Objective-Although diverse functions of angiopoietin-2 (Ang2) have been revealed, little is known about upstream signaling molecules regulating Ang2 exocytosis. We therefore investigated the mechanism of Ang2 exocytosis in human blood and lymphatic endothelial cells (BECs and LECs) by stimulation with sphingosine-1-phosphate (S1P). Methods and Results-By immunostaining and ELISA analyses using our newly developed human Ang2-specific antibodies, Ang2 exocytosis from human endothelial cells was examined. Both ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…In vitro, S1P induces LEC migration and tube formation via the S1P1/G i /PLC/Ca 2+ pathway (70,71). Moreover, S1P stimulates ANG2 secretion from LECs much more potently than from BECs (72). Given that ANG2 is required for lymphatic development (55,56), S1P may act synergistically with ANG2 in lymphangiogenesis.…”
Section: Lymphangiogenic Pathways and Mechanisms Vegfc/d And Vegfr3mentioning
confidence: 99%
“…In vitro, S1P induces LEC migration and tube formation via the S1P1/G i /PLC/Ca 2+ pathway (70,71). Moreover, S1P stimulates ANG2 secretion from LECs much more potently than from BECs (72). Given that ANG2 is required for lymphatic development (55,56), S1P may act synergistically with ANG2 in lymphangiogenesis.…”
Section: Lymphangiogenic Pathways and Mechanisms Vegfc/d And Vegfr3mentioning
confidence: 99%
“…Ang-2 is stored in Weibel–Palade bodies in endothelial cells and secreted upon microenvironmental changes [3033]. Contrary to Ang-1/Tie2 signaling Ang-2 autocrine signaling via the Tie2 receptor results in loss of cell–cell contacts and vascular destabilization (Fig.…”
Section: Ang-2/tie2 Signaling Disrupts Normal Vasculaturementioning
confidence: 99%
“…The sphingolipid S1P is similar to thrombin and histamine in that it can potentiate inflammation in the vasculature via exocytosis of vWF and angiopoietin 2 from WPBs (Matsushita et al, 2004;Jang et al, 2009). Matsushita et al (2004) showed that S1P-mediated exocytosis of WPBs occurs in part via PLCg but also involves extracellular calcium, because both PLC inhibitors and calcium-free media blocked S1P-induced secretion of vWF from human aortic ECs.…”
Section: B Activation Pathways For Exocytosismentioning
confidence: 99%